Application of Position Auction-Based Merit System in Bantul Regency in 2018 - Muhammad Eko Atmojo; Awang Darumurti; Vindhi Putri Pratiwi (Universitas Medan Area, 2021)
This article discusses applying a merit system based on job auctions, especially regarding the mechanism for selecting structural officials in the Bantul Regency. They considered that the merit system is a new method for determining structural positions and has become one of the models that local governments have begun to implement in the placement of civil servants, especially echelon II structural officials. The application of this merit system model is one form of implementing Law Number 5 concerning the State Civil Apparatus. Enforced The application of the merit system because a lot of structural position determinations were not based on competence. Still, the structural position determination was based on proximity and political factors. Therefore, with the existence of this Law, it is significant to immediately implement a merit system so that employees who occupy structural positions are competent and professional people. In data analysis, this study was based on the theory of open selection. The method used in this study was qualitative. The data collection techniques used were interviews and documentation. Based on research conducted that the application of the merit system within the Bantul Regency Government was by applicable regulations, as well as in the application of the merit system using several selection methods including administrative selection, assessment centre method/competency test, paper making, track record tracking, percentage of papers and interviews.